PERAN GANDA PEREMPUAN ANALISIS TEOLOGI FEMINISME - Fatonah, Nur; Nurbaethy, Andi; Indah, Astrid Veranita (Aqidah-ta: Jurnal Ilmu Aqidah, 2024)
The existence of women becomes a complicated issue when women play a dual role, as a domestic worker as well as a public sector worker. Problems will arise when she as a woman is faced with the choice of taking a career opportunity, exploring her potential, and honing her intellectual abilities or staying at home, caring for children, cooking, and sharing tasks with her partner. In the public domain, men and women have the same opportunities to advance their careers which are supported by a person's intellectual and professional level. This is what causes women to want career opportunities in the public sphere, rather than closing themselves off to routine daily problems in the domestic sphere. The dilemma of women in the modern era marks the maturity of thinking in achieving dreams as an intelligent woman who has a successful career in the public sphere while being able to overcome household routines in the domestic sphere. Based on the analysis of feminist theology, it is hoped that it will be able to open public awareness of gender equality in a patriarchal culture